# Solved Examples on Factorization

Covid-19 has led the world to go through a phenomenal transition .

E-learning is the future today.

Stay Home , Stay Safe and keep learning!!!

In this section you can see Solved Examples on Factorization. Go through them carefully and then solve your question.

Solved Examples on Factorization

Using common factor

1) 4x + 8

Here , 4 is a common factor

4( x +2 ) are the factors .

------------------------------------------------------------
2) 8x^2 + 4x

Here , 4x is a common factor

= 4x( 2x +1) are the factors.

-------------------------------------------------------------
3) 3x^3 + 6x^2 + 9

Here, 3 is a common factor

= 3( x3 + 2x23
are the factors.

-------------------------------------------------------------
Using Identities

1) 4x2 + 20 x +25

Here first and last term are perfect square so we will use an identity of
 a2 +2ab +b2 = ( a+b)2

(2x )2 + 2 (2x)(5) +(5)2

=(2x + 5)2

Factors are (2x +5)(2x +5)

---------------------------------------------------------------
2) 9x2 - 6x +1

Here first and last term are perfect square so we will use an identity of
 a2 -2ab +b2 = ( a-b)2

(3x )2- 2 (3x)(5) +(1)2

=(3x - 1)2

-------------------------------------------------------------------
3) a2 - b2 - c2 + d2 - 2(ad - bc)

Solution :
a2 - b2 - c2 + d2 - 2(ad - bc)

= a2 - b2 - c2 + d2 - 2ad + 2bc)

= (a2 + d2 - 2ad) + ( -b2 - c2 + 2bc)

= (a2 - 2ad + d2) - ( b2 - 2bc + c2)

= (a - d)2 - (b - c)2

= ( a - d + b - c)[a - d -(b - c)][ use a2- b2 = (a + b)(a - b)]

= ( a - d + b - c)(a - d - b + c)

-----------------------------------------------------------------
4) a4 - 81

Solution :
a4 - 81

= (a2)2 - (9)2

= (a2 + 9)(a2 - 9)

= (a2 + 9)[a2 -(3)2] [ use a2- b2 = (a + b)(a - b)]

= (a2 + 9)(a + 3)(a - 3) [ use a2- b2 = (a + b)(a - b)]

Factoring

Factorization by common factor
Factorization by Grouping
Factorization using Identities
Factorization of Cubic Polynomial
Solved Examples on Factorization